Developing shoot regeneration protocol for selected cultivars of papaya (carica papaya L.) - Chitraa Devi, A/P Krishnan. (Universiti Malaysia Sarawak (UNIMAS), 2006)
Papaya (Carica papaya L.) 'Onefoot' and 'Exotica II' are commercial fruit trees ofthe Caricaceae. The present study was carried out to develop an in vitro shoot regeneration protocol of papaya 'Exotica II' and 'Onefoot'. This study started with development of a protocol for establishing aseptic cultures. Culturing surface sterilized explants on five different PPM concentrated media showed that there was no significant difference in the various concentration of PPM. However, observation showed that explants in PPM 3 ml/l looked normal and healthier than others. Shoot regeneration protocol developed by culturing shoot-tip and axillary-bud explants of 'Exotica II' and 'Onefoot' in three different culture media which incorporated with 3 ml/l PPM and 10 ml/l Tetracycline. Medium B consists of MS medium supplemented with 1.86 mgll NAA + 0.45 mg/I BAP + 10.76 mg/l Kinetin. Medium C consists ofB5 Medium supplemented with 1.86 mgJl NAA + 1.08 mg/I Kinetin and Medium D consists of MS medium supplemented with 0.2 mg/I NAA + 0.5 mg/I BAP. The best result for multiple shoots regeneration was observed from 'Onefoot' shoot-tip explant in Media B and D. Explant in Medium C produced abnormal multiple shoots thus this media was not suitable for multiple shoots regeneration. Therefore, Media Band D could be used to produce multiple shoots regeneration from 'Onefoot' shoot-tip explant.